Air-conditioning system design manual - Grondzik, Walter T. (ASHRAE professional series., 2007)
The Air Conditioning Manual was written to assist entry-level engineers in the design of air-conditioning systems. It is also suable -- in conjuction with fundamental HVAC & R resourcee material -- as a senior- or graduate-level text for a university course in HVAC system design. The manual was written to fill the void between theory and practice -- to bridge the gap between real-world design practices and the theoretical caluclations and analytical procedures or on the design of components.